Spectrum crispness sensory scale correlation with instrumental acoustic high-sampling rate and mechanical analyses. (March 2020) - Andreani, Pamela; de Moraes, Jaqueline O.; Murta, Bernardo H.P.; Link, Jade V.; Tribuzi, Giustino; Laurindo, João B.; Paul, Stephan; Carciofi, Bruno A.M.
Graphical abstract: Highlights: Products from Spectrum Crispness Scale characterized by instrumental measurements. SPLeq showed the highest linear correlation with the Spectrum Crispness Scale. Penetration test was better than compression test to differentiate the products. Poor correlation between sensory crispness and mechanical parameters were found. Abstract: Mechanical and acoustical instrumental tests can help to predict and compare the sensory crispness of food products. This study proposed a method to correlate crispness sensory analyses to instrumental parameters using the standard products of the Spectrum Crispness Sensory Scale. An acoustic system was developed with a high-sampling rate for characterizing food crispness. Force-displacement and acoustic signals were measured during penetration and compression tests of the products in the Spectrum Scale. A band-pass filter suppressed the texture analyzer's engine and gearbox noise. High correlations were obtained between acoustical and sensory parameters in both tests; however, the penetration test better differentiated the products. The high-sampling rate acoustical measurement system was capable of discriminate crispy products, although the trained sensory panel was still more sensitive to small differences.